A New Series of Heteroleptic Cd(II) Diimine‐Ferrocenyl Dithiocarbamate Complexes which Successfully Co‐Sensitizes TiO2 Photoanode with Ru N719 Dye in DSSC. Issue 27 (21st September 2017) - Manar, Krishna K.; Neetu,; Anamika,; Srivastava, Pankaj; Drew, Michael G. B.; Singh, Nanhai
Abstract: New heteroleptic complexes of the form [Cd(diimine)(Fcdtc)2 ] (diimine= 1, 10‐phenanthroline (phen), Fcdtc=N‐ferrocenyl‐N‐pyridin‐3‐ylmethyl dithiocarbamate (KL1) Cd1 ; 2, 2'‐bipyridyl (bpy), N‐ferrocenyl‐N‐pyridin‐4‐ylmethyl dithiocarbamate (KL2) Cd2 ; bpy, (KL1) Cd3 and phen, (KL2) Cd4 ) have been synthesised and characterized by elemental analyses, spectroscopy (IR, UV‐Vis., 1 H and 13 C 1 H NMR) and their structures have been revealed by X‐ray crystallography. These complexes have been explored as co‐sensitizers with N719 over TiO2 for application as dye sensitized solar cells (DSSC) photoanodes. The use of these complexes as co‐sensitizers resulted in extended UV‐Visible spectral response, greater dye loading, enhanced electron life time, reduced charge recombination and thermodynamically more facile charge transfer in the DSSC. Among all the co‐sensitized cells (Cd1 /N719, Cd2 /N719, Cd3 /N719 and Cd4 /N719), the Cd1‐ based cell demonstrated not only the highest incident photon to current efficiency (IPCE) 47% but the obtained current conversion efficiency 3.84%, was much higher than that of the N719 based cell (2.70%) under the same illumination condition. Abstract : New luminescent Cd(II) diimine‐dithiocarbamate complexes [Cd(diimine)(Fcdtc)2 ] (diimine= 1, 10‐phenanthroline (phen), Fcdtc=N‐ferrocenyl‐N‐pyridin‐3‐ylmethyl dithiocarbamate (KL1) Cd1 ; 2, 2'‐bipyridyl (bpy), N‐ferrocenyl‐N‐pyridin‐4‐ylmethyl dithiocarbamate (KL2) Cd2 ; bpy, (KL1) Cd3 and phen, (KL2) Cd4 ) have been synthesised and characterized by microanalysis and their structures have been elucidated by single crystal X‐ray diffraction. All the four complexes showed efficient co‐sensitizing activities with N719 over TiO2 when employed as DSSC photoanodes.